Erosion and redeposition patterns on entire erosion marker tiles after exposure in the first operation phase of WEST. (7th September 2021) - Balden, M; Mayer, M; Bliewert, B; Bernard, E; Diez, M; Firdaouss, M; Missirlian, M; Pégourié, B; Richou, M; Roche, H; Tsitrone, E; Martin, C; et al.
Abstract: The net erosion and deposition patterns in the inner and outer divertor of WEST were determined after different experimental campaigns (C3 and C4) of the first operational phase using ion beam analyses and scanning electron microscopy techniques. The analyses were performed on four entire tiles from inertially cooled, W-coated divertor units with an additional Mo marker coating covered with a further W coating. Strong erosion occurred at the expected location of the inner and outer strike line area with a campaign-averaged net erosion rate of >0.1 nm s −1 . On the high field side of the inner strike line area, thick deposited layers were found (>10 μ m; growth rate >1 nm s −1 ), mainly composed of B, C, O, and W. Additionally, strong arcing was observed in this region. At the end of the C4 campaign, He discharges were performed to study the He-W interaction. Although the conditions for nanotendrils, i.e. fuzz formation were fulfilled around the outer strike line position, neither nanotendrils nor He bubbles (>10 nm) were observed at this area.